2016
DOI: 10.4238/gmr.15027521
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 tissue expression level is associated with aggressive progression of gastric cancer

Abstract: ABSTRACT. The aim of the present study was to investigate the clinical significance of microRNA-218 (miR-218) in gastric cancer. We enrolled 112 patients having undergone surgery for gastric cancer between May 2008 and June 2014. Expression of miR-218 was determined by real-time quantitative reverse transcription-polymerase chain reaction. Survival curves were plotted using the Kaplan-Meier method and compared by the log-rank test. We found that miR-218 expression was significantly downregulated in gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that miRNAs serve important roles in human cancer biological processes, including initiation, development, migration and metastasis (22)(23)(24)(25)(26). miR-218 can act as a tumor suppressor and is downregulated in various types of human cancer (27)(28)(29)(30)(31). miR-218 can inhibit cancer cell proliferation, invasion, migration, EMT, lymph node metastasis and self-renewal in glioma, cervical cancer, gastric cancer and bladder cancer, among others (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miRNAs serve important roles in human cancer biological processes, including initiation, development, migration and metastasis (22)(23)(24)(25)(26). miR-218 can act as a tumor suppressor and is downregulated in various types of human cancer (27)(28)(29)(30)(31). miR-218 can inhibit cancer cell proliferation, invasion, migration, EMT, lymph node metastasis and self-renewal in glioma, cervical cancer, gastric cancer and bladder cancer, among others (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, we evaluated the expression levels of miR-218 among 359 GC patients in the TCGA dataset and observed that higher miR-218 expression level was associated with a better survival of GC ( P = 0.002). Recent research also confirmed that lower miR-218 tissue expression level was associated with aggressive progression of gastric cancer [30]. Meanwhile, miR-218 could inhibit invasion and metastasis of gastric cancer by targeting the Robo1 receptor [31].…”
Section: Discussionmentioning
confidence: 98%
“…[43] MIR-331 and MIR-218 have been found to regulate the development and progression of various types of cancer cells. [44][45][46][47] Interestingly, the role of the transcription factor target IRF family in the regulation of cell cycle and apoptosis as well as its important function in immune response, immune cell development, and the regulation of tumorigenesis has been emphasized,. [48,49] Thus, TLR1/2/7/8 may regulate cell cycle, apoptosis and immune response in LUAD via these transcription factor targets, kinase targets and miRNA targets.…”
Section: Discussionmentioning
confidence: 99%